Workplace bullying policies, higher education and the First Amendment: Building bridges not walls. Issue 1 (3rd July 2018) - Smith, Frances L. M.; Coel, Crystal Rae
ABSTRACT: The purpose of this article is to demonstrate that higher education institutions should change their Faculty Codes of Conduct to reflect workplace bullying as a form of unacceptable harassment. The article first provides a definition for workplace bullying; secondly, it offers an analysis of how the First Amendment is not an absolute, especially in the workplace; thirdly, it examines the scant legislative and judicial attention that is given to this issue; and finally, an argument is made to show how colleges and universities are not providing clear enough policies and procedures to address workplace bullying. That argument focuses on results of our thematic analysis of 276 Faculty Codes of Conduct from a variety of universities and colleges across the United States. That analysis revealed two primary themes: the Harassment Hang-up and Employee Engagement. Based on this analysis, we conclude that higher education institutions should change their Faculty Codes of Conduct so bullying is defined as a distinctive form of harassment, provide faculty and staff clear communications regarding how to define bullying, and offer guidance for both targets and bystanders of workplace bullying.